Multiple original spellings, living authors and the Code: The case of Malachius raniansis Mawlood, Hammamurad & Abdulla, 2017 (Coleoptera: Melyridae) - Plonski, Isidor S. (Zootaxa, 2021)
The present communication is primarily nomenclaturial–classical taxonomy is only touched in a side note on a diagnosis. It uses technical terminology coined by Alain Dubois, who is interested in the study of the concepts and theory of biological nomenclature (i.e. the “objective connection between the real world of populations of organisms and the world of language” (Dubois & Ohler 1997)), and who discusses the current ‘International Code for Zoological Nomenclature’ [hereafter just called ‘the Code’] in great detail. The terms are explained where necessary–but see also the glossaries in Dubois et al. (2019) and the works by A. Dubois cited below.